FASILITAS DUDUK DI AREA PUBLIK TAMAN KOTA DAN PLAZA GEDUNG PERKANTORAN - Setiadi GS (Universitas Trisakti, 2013)
Abstract Par and rest area are inseperable from human's need to simply sit down and socialize . Although seats in Indonesia have develoved quite far, if wasn't actually originate in Indonesia. Originally, Indonesia traditional houses are